Perbandingan Perjanjian Batal Demi Hukum dan Perjanjian Dapat Dibatalkan dalam Sistem Hukum Indonesia - Wendi Rehan Situmorang; FredySyah Putra; Gracelino Prasetyo Nainggolan; Mario Purba; Jogi Situmorang Siringoringo (Fakultas Hukum, Universitas Sains dan Teknologi Komputer, 2026)
Contract law sits at the heart of commercial life, yet questions about what makes an agreement legally valid or invalid remain a persistent source of confusion in Indonesian legal practice. This study investigates the conceptual and practical distinction between two categories of defective agreements under Indonesian law: void agreements (perjanjian batal demi hukum) and voidable agreements (perjanjian dapat dibatalkan). Employing a normative legal research design grounded in systematic literature review, the study draws on primary sources including the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata), relevant statutes, and Supreme Court decisions, along with five years of secondary materials such as legal textbooks, peer-reviewed journals, and scholarly commentaries. Analysis shows that void agreements fail to satisfy the objective validity requirements of Article 1320(3) and (4) of the Civil Code, rendering them non-existent from the outset and incapable of producing any legal rights or duties. Their nullity is automatic and absolute, requiring no court action and admitting no cure through subsequent ratification. Voidable agreements, by contrast, breach only the subjective requirements of Article 1320(1) and (2) free consent and legal capacity and therefore remain valid and enforceable unless and until a competent party successfully petitions for annulment within the five-year period prescribed by Article 1454. The study also uncovers a troubling inconsistency in lower court rulings that conflate these two distinct concepts, a finding that points to the need for clearer legislative language and stronger judicial guidance. These results carry direct relevance for contract drafting, litigation strategy, and business law education, and the analytical framework offered here is intended as a practical tool for legal educators, practitioners, and commercial actors operating under Indonesian law.